Cattle trypanosomiasis in Africa to 2030 - Thornton, Philip K.; Robinson, Timothy P.; Kruska, Russell L.; Jones, Peter G.; McDermott, John J.; Reid, Robin S. (Office of Science and Innovation, 2006)
Trypanosomiasis diseases are caused by single-cell organisms and affect both humans and cattle. This indicative study modelled the effect of climate change and population growth on the future range of tsetse flies, their main vector, in sub- Saharan Africa. Projected climate change to 2030 has a limited effect on their distribution. Population growth has more significant consequences, mainly caused by the land-use change that accompanies it. It could reduce the area in which tsetse flies are found by 15% by 2030. The main effect would be in drier areas of western, eastern and southern Africa, and in Ethiopia. Humid areas would be less altered. The authors say that other factors such as disease control efforts and changing agricultural practices may also affect the future range of the flies and of the diseases with which they are associated.